2017
DOI: 10.3390/ijms18112480
|View full text |Cite
|
Sign up to set email alerts
|

Altered Aconitase 2 Activity in Huntington’s Disease Peripheral Blood Cells and Mouse Model Striatum

Abstract: Huntington’s disease (HD) is caused by an unstable cytosine adenine guanine (CAG) trinucleotide repeat expansion encoding a polyglutamine tract in the huntingtin protein. Previously, we identified several up- and down-regulated protein molecules in the striatum of the Hdh(CAG)150 knock-in mice at 16 months of age, a mouse model which is modeling the early human HD stage. Among those molecules, aconitase 2 (Aco2) located in the mitochondrial matrix is involved in the energy generation and susceptible to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…After transferring the supernatant into a new tube, samples centrifuged for 10 min (20,000× g, 4˚C). The resulting pellet was re-suspended in icecold 0.2 mM sodium citrate and then sonicated for 20 s [22]. Before the enzymatic assays, the extract was further diluted and protein concentration of samples were determined using Bradford method [21].…”
Section: Mitochondria Isolation From Pbmcsmentioning
confidence: 99%
“…After transferring the supernatant into a new tube, samples centrifuged for 10 min (20,000× g, 4˚C). The resulting pellet was re-suspended in icecold 0.2 mM sodium citrate and then sonicated for 20 s [22]. Before the enzymatic assays, the extract was further diluted and protein concentration of samples were determined using Bradford method [21].…”
Section: Mitochondria Isolation From Pbmcsmentioning
confidence: 99%
“…The primary activity of ACO2 protein is to control cellular adenosine triphosphate (ATP) production via conversion of citrate to isocitrate . Mutations or altered activity of ACO2 are associated with diseases such as epilepsy, brain atrophy, optic atrophy, retinal degeneration, and Huntington's Disease . Our results showed that ACO2 protein increased by 60% in ISCA1 knockout embryos (Figure A,C), unlike the observed decrease in Fe/S transfer protein.…”
Section: Discussionmentioning
confidence: 66%
“…Our results showed that ACO2 protein increased by 60% in ISCA1 knockout embryos (Figure A,C), unlike the observed decrease in Fe/S transfer protein. ACO2 is central to carbohydrate and energy metabolism and is associated with multiple metabolic pathways and pathologic conditions such as Huntington's Disease, hypoxia, and reactive oxygen species (ROS) and energy metabolism defects . ACO2 production could be regulated by cell energy metabolism and the observed increase in ACO2 activity might counteract cell energy metabolism defects .…”
Section: Discussionmentioning
confidence: 99%
“…Since then, additional reports described that autosomal recessive Aco2 mutations can cause either isolated or syndromic optic neuropathy 54 . Decreased Aco2 activity was found in the peripheral blood mononuclear cells of both Huntington's disease patients and presymptomatic Huntington's disease mutation carriers 55 . Also, a homozygous missense mutation was identified in the Aco2 gene (c.1240T > G p. Phe414Val) that segregated with hereditary spastic paraplegia complicated by intellectual disability and microcephaly 56 .…”
Section: Discussionmentioning
confidence: 99%